Krig i sandlådan: En komparativ studie om rättfärdigt krig i USA-Venezuela konflikten och Gulfkriget - Hasewinkel,Oscar; Eriksson,Elis (2026)
The idea of a just war is as old as war itself. This paper examines the ongoing conflict between the United States and Venezuela, as well as the Gulf War, and analyzes how they relate to just war theory, with a particular focus on jus ad bellum. The purpose of this thesis is to provide an empirical study of an otherwise theoretical subject in order to assess the viability of the theory in modern warfare. The study is a comparative case study of the U.S.–Venezuela conflict and the Gulf War, using four analytical variables to determine how justified these conflicts were or are. These variables are derived from the theoretical framework, primarily based on Michael Walzer and his work Just and Unjust Wars. Other relevant works, such as Vom Kriege by Carl von Clausewitz, are used to supplement the theoretical perspective. The source material selected for this thesis consists of articles relevant to the U.S.–Venezuela conflict, the book The Room Where It Happened by John Bolton, Secret Dossier: The Hidden Agenda Behind the Gulf War by Pierre Salinger and Eric Laurent, as well as congressional records from 10–12 January 1991.The results of the study indicate that a U.S. attack on Venezuela is not justified according to the selected variables. In contrast to the justified U.S. participation in the Gulf War, the Trump administration does not adhere to established democratic practices. While just war theory remains viable within the field of political science, it appears to have lost its political relevance with regard to the U.S.–Venezuela conflict.
Keywords: USA; Venezuela; Irak; Kuwait; rättfärdigt krig; Gulfkriget; jus ad bellum.